P178 Does current strength interact with baseline performance to influence tDCS outcome? A replication study. Issue 3 (March 2017) - Learmonth, G.; Benwell, C.; Thut, G.; Harvey, M.
Abstract : Introduction: TDCS studies have recently faced strong criticism for exhibiting both a large intra- and inter-subject response variability and a low reproducibility of effects. We here attempt to replicate one of our own recent studies. In this study, we found a rightward shift of spatial attention bias, relative to a leftward ("pseudoneglect") bias at baseline (as indexed by the landmark task ) using a bi-hemispheric montage (P5-aTCS/P6-cTDCS, Dual tDCS) to affect the balance of activity between the left versus right posterior parietal cortices (PPCs). This effect was overall weak (near significant trend in 40 participants), but displayed a complex, non-linear interaction between current strength and baseline task performance, indicating inter-individual variability in sensitivity to tDCS according to baseline state and intensity. Objectives: Using a within-subjects design (vs between-subjects in our previous study) to further test and replicate baseline state- and intensity-dependency of tDCS outcome. Methods: 20 adults received 1 mA & 2 mA Dual, and Sham tDCS, counterbalanced across different days. In each session, 6 blocks of the landmark task were completed (2 pre-tDCS, 2 during-tDCS and 2 post-tDCS). Dual tDCS was applied for 15 min (Sham = 30 s). Subjects were divided into good/poor baseline performance groups. Results: We found no overall effects of tDCS on landmark task performance, nor any interaction with the factors baseline state or tDCS intensity. Our data are however not fully conclusive as there are group-level spatial bias differences at baseline between the 3 testing sessions that may confound the results (and were not present in our previous study). Further recordings are needed to resolve this point (that we hope to present at the conference). Conclusion: We believe more replication studies (within- or across participants) are needed to establish reproducibility of tDCS effects.